Analisis Literatur Tentang Model Pembelajaran Problem Based Learning Dalam Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam - Marliyah, Marliyah; Aulia, Lina; Arifah, Iif; Juhji, Juhji (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
The problem based learning model is an approach proposed to improve students' natural science learning outcomes. This study aims to investigate the influence of PBL on science learning outcomes in elementary schools through systematic literature analysis. The literature study method was used to analyze ten scientific articles related to PBL and science learning outcomes in elementary schools. The results of the analysis show that PBL is effective in stimulating interest in learning, strengthening critical thinking skills, and improving problem-solving abilities in a scientific context. The implication of this research is the need for support in training and professional development for educators, as well as further research to identify key factors that influence the success of PBL implementation. The integration of PBL into the science education curriculum needs to be strengthened through collaboration between education stakeholders. Thus, the use of PBL is expected to improve students' science learning outcomes in a holistic and sustainable manner.